Meningkatkan Literasi Keuangan dan Kesadaran Lingkungan melalui Edukasi Kreatif untuk Anak-Anak di Desa Jembayan Dalam - Margareth Henrika; Annisa Mawardah (Jurnal Ragam Pengabdian, 2025)
This study examines the impact of the "Gemar Menabung dengan Celengan Kreatif" program on enhancing financial literacy and saving habits among elementary school children in rural areas. The program integrates creativity with financial education by involving students in hands-on activities, such as creating piggy banks from recycled bottles. The aim was to foster an understanding of saving and financial management while also raising environmental awareness. Using a combination of pre-test and post-test assessments, as well as qualitative methods like interviews and observations, the study evaluates the effectiveness of this creative educational approach. The results demonstrate significant improvements in the children’s understanding of financial concepts, with increased motivation to save. The hands-on nature of the activities led to higher engagement, and students showed a greater understanding of the link between money management and their daily lives. Additionally, the creative aspect of the program contributed to increased environmental consciousness. This study contributes to the existing body of knowledge by highlighting the effectiveness of integrating financial literacy with creative projects in rural education. The findings suggest that similar programs could be scaled up in other rural areas, providing valuable insights for further research on long-term behavioral changes and the role of community involvement in financial education.